(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2013)
The most extensive judicial holidays are not a benefit granted only in Brazil. Several countries establishing career plan for their magistrates court to make the activity more attractive to legal professionals. Other activities also enjoy benefits of different regimes. They are justified in both Brazil and the world by the degree of responsibility and duties imposed on judges, not to mention the stress caused by the effective exercise of judicial activity.